2017
DOI: 10.1186/s12938-017-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

A medium invasiveness multi-level patient’s specific template for pedicle screw placement in the scoliosis surgery

Abstract: BackgroundSeveral methods including free-hand technique, fluoroscopic guidance, image-guided navigation, computer-assisted surgery system, robotic platform and patient’s specific templates are being used for pedicle screw placement. These methods have screw misplacements and are not always easy to be applied. Furthermore, it is necessary to expose completely a large portions of the spine in order to access fit entirely around the vertebrae.MethodsIn this study, a multi-level patient’s specific template with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
1
10
0
7
Order By: Relevance
“…Among the 18 dogs that underwent surgery, 15 (83.3%) exhibited clinical benefits at the mid-term follow up evaluation; therefore, the success rate of our surgical technique was at least similar, if not superior, to those of previous studies utilizing other surgical techniques for AAI stabilization [3, 4, 7, 10]. Similar technology has already been investigated in the area of orthopedics [15] [16], oral-facial surgery [1719], and neurosurgery [20, 21] for the patient-specific manufacture of surgery guides and implants. In veterinary literature, investigation of patient-specific 3D printed drill guide for placement of cervical transpedicular screws was reported most recently [22].…”
Section: Discussionsupporting
confidence: 70%
“…Among the 18 dogs that underwent surgery, 15 (83.3%) exhibited clinical benefits at the mid-term follow up evaluation; therefore, the success rate of our surgical technique was at least similar, if not superior, to those of previous studies utilizing other surgical techniques for AAI stabilization [3, 4, 7, 10]. Similar technology has already been investigated in the area of orthopedics [15] [16], oral-facial surgery [1719], and neurosurgery [20, 21] for the patient-specific manufacture of surgery guides and implants. In veterinary literature, investigation of patient-specific 3D printed drill guide for placement of cervical transpedicular screws was reported most recently [22].…”
Section: Discussionsupporting
confidence: 70%
“…In our review, 3DP applications, including 3DP screw guides and planning models, have resulted in statistically decreased operative durations and increased pedicle screw placement accuracy. 1,18,19,28,31 Compared with conventional imaging (eg, intraoperative fluoroscopy), 3DP screw placement guides provide improved screw placement accuracy rates, 19,20,[31][32][33][34][35] and models enhance intrateam communication and planning, 21,[23][24][25]28,36 and reduced fluoroscopy time. 19,20 In one retrospective study of 126 adolescent idiopathic scoliosis patients with a Lenke 1 deformity, Yang et al 1 showed that 3DP models used for surgical planning resulted in reduced operative duration and blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Эти свойства модели в значительной степени определяются субъективными впечатлениями, для объективизации которых необходимо проведение опросного исследования. Имеются указания на такой недостаток навигационного шаблона, как необходимость тщательного скелетирования задних структур позвонков, что приводит к большей крово-потере и травматизации тканей [29]. Вместе с тем планирование артродезирующей операции само по себе требует скелетирования задних структур как одного из условий формирования полноценного локального костного блока.…”
Section: Discussionunclassified
“…Таким образом, при транспедикулярной фиксации в маломобильной зоне предпочтительно использование единого навигационного шаблона, что позволяет более надежно позиционировать опорную площадку, а также минимизировать затраты времени, связанные с последовательной установкой нескольких шаблонов. В свою очередь, применение многоуровневого шаблона, состоящего из нескольких опорных площадок, соединенных гибкими вставками, представляется излишним [29].…”
Section: Discussionunclassified